Kesejahteraan Mahasiswa Pelaku Bisnis Online di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sumatera Utara - Rafly, Rafly; Randa Putra Kasea Sinaga (Yayasan Literasi Sains Indonesia, 2024)
One way for students to achieve prosperity, especially economically, is to build an online business. An online business is a business that is marketed via the internet in various ways so that it can make money. This study aims to find out and analyze how the welfare of online business students at the Faculty of Social and Political Sciences, University of North Sumatra, The research subjects were students who became online business people at the Faculty of Social and Political Sciences, University of North Sumatra. This type of research is qualitative and uses primary data collection techniques through observation and interviews as well as secondary data based on qualitative audio-visual documents and materials. The results obtained from this study show that students are able to gain economic benefits by doing business online. They are able to pay their own tuition fees and also do not ask their parents for pocket money, helping their family's economy. In addition, students earn non-monetary income by adding insight into digital technology, business understanding, and business relations. The conclusion of the research is the fulfillment of monetary income; this is evidenced by the statements of informants who stated that they have been able to meet their daily needs after running an online business and fulfilling non-monetary income. After running an online business, students gain an understanding of digital technology, business understanding, and also relationships that are able to help develop their business.